Environmental Fate of Emerging Organic Micro-Contaminants - Hooda, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The toxicity and fate of pharmaceuticals and other emerging micro-organic contaminants in the natural and built environments have been the focus of much research over the last twenty years. Particular focus has recently centred on the fate of antimicrobial chemicals, including antibiotics and antifungals. The occurrence of such chemicals in the environment is thought to contribute to the selection of resistance in exposed microorganisms.This Special Issue (SI) brings together a broad range of recent advances in the field of emerging micro-organic contaminants, ranging from medicinal contaminants to industrial chemicals in the environment. Notably, these range from chemical extraction and large-scale analysis to adverse effects on non-target aquatic organisms and potential risk to humans via contaminated foodstuffs. Additionally, this Special Issue also presents novel contaminant treatment/degradation methods of both physical and biological nature.